1991
DOI: 10.1161/01.hyp.18.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of hypertension in the sinoaortic-denervated spontaneously hypertensive rat.

Abstract: The present study was performed to examine the relation between the gain of the baroreceptor reflex and the pathogenesis of hypertension in the spontaneously hypertensive rat Spontaneously hypertensive or Wistar-Kyoto rats underwent either sinoaortic baroreceptor denervation or sham denervation at 28-35 days of age. Four months later these rats were chronically instrumented for measurements of arterial pressure and heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
3
11
1
Order By: Relevance
“…In this way, the long-term control of arterial pressure occurs independently of arterial baroreceptor input. Such result is in agreement with Osborn [26]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this way, the long-term control of arterial pressure occurs independently of arterial baroreceptor input. Such result is in agreement with Osborn [26]. …”
Section: Discussionsupporting
confidence: 93%
“…In all studies in which these receptors were denervated, blood pressure oscillations increased significantly while mean arterial pressure (MAP) did it only for a few days [19-26]. Even when both carotid and aortic baroreceptors and chemoreceptors were removed, MAP increased only for a short period of time [27].…”
Section: Antecedentsmentioning
confidence: 99%
“…These results suggest that a normally operating arterial baroreceptor reflex is required to prevent chronic salt-induced increases in arterial pressure. This idea is not compatible with previous studies that have shown that SAD did not affect chronic regulation of arterial pressure in experimental 14 ' 15 or spontaneous 9 hypertension. The implication of these previous findings is that, although the baroreceptor reflex acutely buffers changes in blood pressure, chronic regulation of pressure is not dependent on this reflex because of the resetting properties of arterial baroreceptors.…”
Section: Figure 2 Line Plots Show Nacl-induced Changes In Sodium Andcontrasting
confidence: 96%
“…1 Dynamic characteristics of the arterial baroreflex are also preserved in SHR. 16,17 While sino-aortic baroreceptor denervation does not affect the development of hypertension in SHR, 26 it is likely that the carotid sinus baroreflex preserved the ability to reduce AP to within a normal pressure range. The present study results might provide a rationale for the use of a carotid baroreceptor stimulator as an alternative therapy for drug-resistant hypertension.…”
Section: Baroreflex Total-loop Characteristics In Wky and Shrmentioning
confidence: 99%